A Hille-Wintner type comparison theorem for second order difference equations - John W. Hooker (International Journal of Mathematics and Mathematical Sciences)
For the linear difference equation Δ(cn−1Δxn−1)+anxn=0   with   cn>0, a non-oscillation comparison theorem given in terms of the coefficients cn and the series ∑n=k∞an, has been proved.